Clinical Outcomes of Arthroscopic 360° Capsular Release for Idiopathic Adhesive Capsulitis in Beach Chair Position. (Journal of Pakistan Orthopaedic Association, 2023)
Objective: To study the clinical consequences Outcome after Arthroscopic 360 capsular release in beach Chair position for Idiopathic Adhesive Capsulitis (Frozen Shoulder) that had not been improved after any other intervention for at least 6 months.Methodology: In this study, 40 shoulders were examined in 40 participants who had adhesive capsulitis and had arthroscopic capsular release between 2018 to 2022 in Jinnah Hospital, Lahore. An ordinary Follow-up examination was were conducted at 3, 6, and 9 months after Post procedure (Follow up rate was 90 %). Preoperatively and at the follow-up exam following surgery, Range of motion and pain were assessed. Preoperatively and postoperatively, pain and Range of motion were compared using statistical analysis SPSS Version 21. Level of significance was set at p